Proses Pembuatan Mesin Injection Molding Hand-Press untuk Plastik Komposit - Alfan Ekajati Latief; Nuha Desi Anggraeni; Wildhan Rhamdani (Department of Mechanical Engineering, Universitas Andalas, 2020)
Injection molding is a method of forming thermoplastic material that is melted due to heating. The heating result is then injected by the nozzle into the mold until the thermoplastic material hardens. Plastic processing using injection molding is used to produce strong thermoplastic material quickly. The manufacture of injection molding machine hand-press is expected to help the process of plastic processing that demands material engineering and manufacturing technology. Research in the process of making injection molding machine hand-press aims to determine the manufacturing process time and temperature when the operation of injection molding hand-press. The process of making injection molding hand-press shows that the required time is 612 minutes, while in theory the time is 565.3 minutes. The operating temperature is (230-260) °C, with an optimum temperature of 250 °C.